Diseño y Análisis del sistema motriz, guiado y enderezado de alambre en un banco para simular el proceso de trefilado (2021)
In the different types of existing wire drawing machines, there is evidence of the lack of study and monitoring of variables within the process, mainly speed and traction force, factors that directly affect the improvement in the quality level and production of drawn wire, which is translates into little monitoring of factors that cause the breakage of the wire and production stops, which leads to generate a diversification of different proposals to be able to carry out the correct observation and implementation of unusual systems, to carry out an industrial analysis within of the academic, for which it is necessary to carry out the ideation and subsequent implementation of a motor, guided and straightened system in an adaptive bench for the teaching and study of the drawing process